2017
DOI: 10.1097/lgt.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Vulvodynia: What We Know and Where We Should Be Going

Abstract: Standardized nomenclature will allow for comparability of studies and progress in research related to the pathophysiology of VVD and to facilitate clinical decision making and treatment choices. Although the current understanding of the pathogenesis of VVD is limited, there are new opportunities to explore potential diagnostic markers differences in women with VVD, which may lead to targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…The sociodemographic characteristics reported in various studies [ 41 , 42 , 43 , 44 ] show that vulvodynia is prevalent in women under the age of 30. Other research indicates that more than 75% of female patients are less than 34 years old and most of them are under 25 years old [ 2 , 10 , 15 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sociodemographic characteristics reported in various studies [ 41 , 42 , 43 , 44 ] show that vulvodynia is prevalent in women under the age of 30. Other research indicates that more than 75% of female patients are less than 34 years old and most of them are under 25 years old [ 2 , 10 , 15 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…No correlations were found in the literature regarding vulvodynia in the context of isolated parameters, but correlations are observed in the area of BMI. Indeed, Naess I and Bø K. [ 44 ] showed that vulvodynia appeared more often in individuals with a low BMI. Another study on the remission of the disease conducted by Nguyen RH.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical expression of VVS, many pathological mechanisms are involved [ 22 ]. The inflammatory aspect has a key role in generating the main symptoms of this syndrome [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the microbiome in VVS patients showed a prevalence of Streptococcus, Gardnerella, Enterococcus, and Candida albicans spp. [ 7 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, altered inflammatory response, associated with the VMB and discovered by molecular methods, may ultimately be linked to vulvodynia by VMB-mediated activation of nociceptive neurons. [105][106][107] Aiming to identify possible etiologies for bothersome vulvovaginal symptoms of pain and vaginitis, Mitchell et al 108 evaluated microbial and immunologic characteristics of women with "idiopathic vaginitis" (defined as moderate-severe vaginal discharge, itching, and irritation without a diagnosis) and vulvodynia and compared them with healthy women. Although G. vaginalis was less prevalent in women with vulvodynia (7% vs 31% in controls and 25% in idiopathic vaginitis, p = .03), there was no significant difference between the groups.…”
Section: The Vaginal Microbiome Nonspecific Symptoms and Vulvodyniamentioning
confidence: 99%